2016
DOI: 10.21475/ajcs.2016.10.04.p7286x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evaluation of Ethiopian sweet sorghum germplasm and their contribution to regional breeding programs

Abstract: Sweet sorghum is an excellent feedstock for ethanol production and is also used for food and livestock feed. Germplasm collection and characterization in sweet sorghum is a crucial step towards breeding and development of superior genotypes for various enduses. In the present study, 13 Simple Sequence Repeat (SSR) markers were used for genotyping 175 Ethiopian s weet sorghum accessions alongside 27 improved accessions from eastern and southern Africa. All the tested markers detected 159 alleles and a high poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
1
14
1
Order By: Relevance
“…Similarly, second highest frequency (29%) was observed for allele size ranged from 151 to 200 bps followed by allele sizes between 100 to 150 bps between ranging (Table 1). In general, the majority of the screened polymorphic markers (94%) allele sizes ranged from 100 to 300 bp which is in agreement with many studies undertaken in the past (Bhattramakki et al, 2000;Kong et al, 2000;Menz et al, 2002;Scholes et al, 2002;Wu et al, 2006;Ramu et al, 2009Disasa et al, 2016a. Besides, most of the markers that their fragment sizes lie in this range showed clear and longer beaks while scoring using GenMapper software (Fig 1) indicated that they should be the choice of marker for the application in sorghum improvement programs.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similarly, second highest frequency (29%) was observed for allele size ranged from 151 to 200 bps followed by allele sizes between 100 to 150 bps between ranging (Table 1). In general, the majority of the screened polymorphic markers (94%) allele sizes ranged from 100 to 300 bp which is in agreement with many studies undertaken in the past (Bhattramakki et al, 2000;Kong et al, 2000;Menz et al, 2002;Scholes et al, 2002;Wu et al, 2006;Ramu et al, 2009Disasa et al, 2016a. Besides, most of the markers that their fragment sizes lie in this range showed clear and longer beaks while scoring using GenMapper software (Fig 1) indicated that they should be the choice of marker for the application in sorghum improvement programs.…”
Section: Discussionsupporting
confidence: 88%
“…The computed average PIC value (0.53) in this experiment was very close to most of the previously reported values using both grain and sweet sorghum (Agrama and Tuinstra,2003;Caniato et al, 2007;Ali et al, 2008;Wang et al, 2009;Ramu et al, 2013). However, the result was somewhat lower than the average PIC value reported in wild sorghum (Muraya et al, 2011;Adugna et al, 2012) and sweet sorghum (Disasa et al, 2016a) populations. This is possibly due the polymorphic nature of the selected SSR markers used for genotyping as well as type of germplasm studied.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Sorghum bicolor (L.) Moench is a member of the Poaceae family and considered as multi-beneficial crop with various uses. The grains are used for food, the leaves are used as animal feed, and the stem with high sugar content is processed for syrup, beverage, and biofuel (Dahlberg et al 2011, Disasa et al 2016. Accordingly, three variants of S. bicolor are known namely grain sorghum, forage sorghum, and sweet sorghum.…”
Section: Introductionmentioning
confidence: 99%